2019
DOI: 10.3389/fnhum.2019.00422
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Action Observation Network in Apraxia After Stroke

Abstract: Limb apraxia is a syndrome often observed after stroke that affects the ability to perform skilled actions despite intact elementary motor and sensory systems. In a large cohort of unselected stroke patients with lesions to the left, right, and bilateral hemispheres, we used voxel-based lesion-symptom mapping (VLSM) on clinical CT head images to identify the neuroanatomical correlates of the impairment of performance in three tasks investigating praxis skills in patient populations. These included a meaningles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 106 publications
(185 reference statements)
0
19
0
Order By: Relevance
“…95 Further dissociations of functional deficits from lesions have been identified in the ventral stream. The superior temporal sulcus is part of the body schema and pantomime network implicated in representing biological motion and other's actions, 10,46,84,104 whereas the inferotemporal area and adjacent inferior occipital lobe regions are thought to have a greater role in the representation of hand posture and handobject interactions. [100][101][102] There are projections from the superior temporal sulcus to the inferior parietal cortex, which is a relevant pathway for observing object-related actions 82,83 (part of this pathway is depicted schematically in Figure 2).…”
Section: Occurrencementioning
confidence: 99%
“…95 Further dissociations of functional deficits from lesions have been identified in the ventral stream. The superior temporal sulcus is part of the body schema and pantomime network implicated in representing biological motion and other's actions, 10,46,84,104 whereas the inferotemporal area and adjacent inferior occipital lobe regions are thought to have a greater role in the representation of hand posture and handobject interactions. [100][101][102] There are projections from the superior temporal sulcus to the inferior parietal cortex, which is a relevant pathway for observing object-related actions 82,83 (part of this pathway is depicted schematically in Figure 2).…”
Section: Occurrencementioning
confidence: 99%
“…According to this, damage to the left parietal lobe was involved in 'ideomotor' deficits as it transforms movement ideas into 'innervatory engrams', which were implemented within sensory-motor areas bilaterally Marsden 2000, Goldenberg, 2009). He termed 'limb-kinetic' apraxia a further deficit in transforming the movement plans into an appropriate selection of muscle synergies to perform a Pizzamiglio et al 2019). In some tasks, both dorsal and ventral stream lesions appear to be involved in apraxia (Vry et al 2012, Buxbaum et al 2014.…”
Section: Classical Work Bymentioning
confidence: 99%
“…recognizing that the executed action matches what was originally shown (Blakemore et al 2000). Moreover, there is recent evidence that meaningless imitation may use action recognition pathways (Pizzamiglio et al 2019). A study in stroke patients, with and without apraxia, showed improved imitation of 'meaningless' gestures if they were perceived to be more familiar (Achilles et al 2016).…”
Section: The Role Of Tasks Used In Apraxia Modelsmentioning
confidence: 99%
“…The imitation task used in this study involved single gesture imitation. According to Makuuchi and Pizzamiglio et al [16,17], we prepared 70 different hand gestures, including those involving the left hand, right hand, and both hands. We used finger coordination and palm orientation as variables, and generated 70 gesture images (25 for the left hand, Brain Sci.…”
Section: Imitation Taskmentioning
confidence: 99%